2010
DOI: 10.1016/j.ijimpeng.2009.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic enhancement of blast-resistant ultra high performance fibre-reinforced concrete under flexural and shear loading

Abstract: Two independent projects are described in which drophammer techniques are used to investigate the dynamic increase factor (DIF) under both flexural and shear high-speed loading of a new ultra high performance fibre reinforced blast resistant concrete. The results from both studies correlate well. The results show that a DIF of the flexural tensile strength rising from 1.0 at 1 s -1 on a slope of 1/3 on a log (strain rate) versus log (DIF) plot can be used for design purposes. The results also show that no DIF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(96 citation statements)
references
References 9 publications
0
96
0
Order By: Relevance
“…Due to the specific cementitious system of UHPC (very small water/binder ratio and relatively high SP amount), it is observed that the pozzolanic reaction of FA is significantly retarded, which causes that a very limited amount of FA can react with Ca(OH) 2 after curing for 91 days. Makita T. [76] Máca P. [77] Habel K. [78] Wang W. [79] Habel K. [80] Corinaldesi V. [81] Millard S.G. [82] S.L. Yang [14] Deeb R. [83] Yazici H. [84] Reference in this study y = 6.003x + 62.732 R 2 = 0.854 Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the specific cementitious system of UHPC (very small water/binder ratio and relatively high SP amount), it is observed that the pozzolanic reaction of FA is significantly retarded, which causes that a very limited amount of FA can react with Ca(OH) 2 after curing for 91 days. Makita T. [76] Máca P. [77] Habel K. [78] Wang W. [79] Habel K. [80] Corinaldesi V. [81] Millard S.G. [82] S.L. Yang [14] Deeb R. [83] Yazici H. [84] Reference in this study y = 6.003x + 62.732 R 2 = 0.854 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…11. Comparison of embedded CO 2 emission of the developed eco-friendly UHPC (EUHPC) and other UHPCs or UHPFRCs [14,[75][76][77][78][79][80][81][82][83][84].…”
Section: Discussionmentioning
confidence: 99%
“…Impact by a high speed point load, such as a bullet, has similarities with a small standoff blast (Millard et al, 2009) and this has informed the test methodology. An explosion near a concrete wall causes a high speed compressive stress wave to load the front face of the wall (Millard et al, 2009), resulting in initial front face spalling Almansa and Canovas (1999).…”
Section: Impact Analysis On Concrete Structuresmentioning
confidence: 99%
“…The sides of the specimen were damaged severely. The deflection was 295 mm on the left side and 310 mm on the 07005-p. 2 The area of the puncture is 0.26m 2 , volume 0.08m 3 , which represents 2.9% of the total volume of the specimen. Total volume of the damaged concrete (puncture + spalling) is 0.15m 3 , which represents 5.6% of the total volume of the specimen.…”
Section: Results Of the Experimentsmentioning
confidence: 99%
“…This rebound causes tensile stresses at the soffit of the material (as described in [2]). The concrete in the concrete cover is not able to cover these tensile stresses and spalls of the specimen (Fig.…”
Section: Behavior Of the Blast Pressure Wave In The Concrete; Concretmentioning
confidence: 99%